Interactive language learning activities for learners’ communicative ability - Siti Fatimah Omar; Haslinda Sutan Ahmad Nawi; Tengku Shahrom Tengku Shahdan; Rita Wong Mee Mee; Lim Seong Pek; Fatin Syamilah Che Yob (Institute of Advanced Engineering and Science, 2020)
Learners’ communicative in English language has been unsatisfactory due to the factors that affect their self-confidence and motivation to speak. However, the problem persisted even though ways were used to overcome the lack of communicative ability among learners in Malaysia. Therefore, this study was conducted to address learners’ perceptions of interactive language learning activities in improving English-speaking ability. The study aimed to analyse the effectiveness of the interactive language learning activities in motivating learners to speak in language classroom. A set of questionnaires containing two sections with 30 questions was administered. There were 50 primary school learners selected randomly to participate in this study. The results were collected and presented in the form of tables. The finding showed that self-confidence, motivation and learning environment affect the learners’ English language speaking ability and the results indicated that interactive language learning activities are able to overcome problems pertaining to communicative in language classroom. In conclusion, interactive language learning activities improved the learners’ English language speaking ability.